Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Ex 8.4, 3 Simplify. (i) (𝑥^2−5) (𝑥+5)+25Here, there are 2 expressions: 1st expression = (𝑥^2−5) (𝑥+5) 2nd expression = 25 Solving 1st expression (𝒙^𝟐−𝟓) (𝒙+𝟓) = 𝑥^2 (𝑥+5)−5(𝑥+5) = (𝑥^2 × 𝑥)+(𝑥^2 × 5)−(−5 × 𝑥)−(5 × 5) = 𝒙^𝟑+𝟓𝒙^𝟐−𝟓𝒙−𝟐𝟓 Now, our expression is (𝒙^𝟐−𝟓) (𝒙+𝟓)+𝟐𝟓 = 𝑥^3+5𝑥^2−5𝑥−25+25 = 𝒙^𝟑+𝟓𝒙^𝟐−𝟓𝒙

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.